Implementing the Internet of Things in a Web-Based Air Pollution Detection System using NodeMCU - Afifuddiin, Mohammad; Wijayanti, Aris; Arifia, Amaludin (KH. A. Wahab Hasbullah University, 2025)
Air pollution is one of the factors that causes health problems. Air pollution can be caused by several factors, two of which are natural factors and human factors. Plumpang District is one of the areas in Tuban Regency where there are many mining and industrial activities, especially limestone processing. Of course, this will cause an increase in the production of pollutant gases that are harmful to the body, one of which is carbon monoxide (CO). The use of the Internet of Things (IoT), microcontrollers, and sensors is expected to create a real-time air pollution monitoring tool. In this study, the MQ-7 sensor was used to detect carbon monoxide gas, and NodeMCU was used as a means of processing data to send data to the database. And later the information from the sensor readings will be displayed on the website page. The results of this study have succeeded in creating a real-time air pollution monitoring system which can then be developed to monitor air pollution itself.